1990
DOI: 10.1016/0014-5793(90)80530-v
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the newly cloned low‐density‐lipoprotein receptor related protein (LRP) is the α2‐macroglobulin receptor

Abstract: The human placental receptor (cQMR) for a*-macroglobulin-proteinase complexes contains 3 polypeptides of approx. 500 kDa, 85 kDa, and 40 kDa. N-terminal sequence analysis of the 500 kDa and 85 kDa polypeptides, analysis of a random selection of peptides covering 536 residues from these polypeptides, and analysis of a 1772 bp cDNA encoding part of the 500 kDa polypeptide provide evidence that the 500 kDa and 85 kDa chains are the a-and p-subunits, respectively, of a recently cloned hepatic membrane protein, ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
133
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 304 publications
(136 citation statements)
references
References 27 publications
3
133
0
Order By: Relevance
“…C-terminal domain (RBD) [11] to an endocytosing receptor known as c%M receptor/low density lipoprotein receptor-related protein (a2MR/LRP) [12][13][14]. Electron microscopic studies [15,16] have shown that the receptor-binding domains of human %M are located at the tips of the H-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…C-terminal domain (RBD) [11] to an endocytosing receptor known as c%M receptor/low density lipoprotein receptor-related protein (a2MR/LRP) [12][13][14]. Electron microscopic studies [15,16] have shown that the receptor-binding domains of human %M are located at the tips of the H-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of c~Ms exposes a previously concealed receptor binding domain, important for the rapid clearance from the circulation [3][4][5]. The receptor for transformed czMs termed ~zMR/LRP [6][7][8] consists of a 515 kDa ligand binding s-chain and a 85 kDa membrane spanning fl-chain [9][10][11]. ~2MR/LRP is present in many tissues, including fibroblasts, adipocytes, macrophages and hepatocytes [3,5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…~2MR/LRP is present in many tissues, including fibroblasts, adipocytes, macrophages and hepatocytes [3,5,12,13]. In addition to ~M-proteinase complexes the receptor binds ligands of several classes, such as plasminogen activator inhibitor-plasminogen activator complexes, lipoprotein lipases and c~2-macroglobulin receptor associated protein (~2M-RAP) [6,10,11,[14][15][16][17][18]. *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The receptor for transformed a2 M is termed a2MR/ LRP [6][7][8]. The 515 kDa a-chain of a2MR/LRP is ligand binding whereas its 85 kDa fl-chain is membrane spanning [9][10][11].…”
Section: Introductionmentioning
confidence: 99%